Development and Evaluation for the Preoperative Nursing Practice Guidelines in Patients with Colorectal Cancer. - Sawettikamporn, Wilai; Chaiviboontham, Suchira; Youngcharoen, Phichpraorn (Pacific Rim International Journal of Nursing Research)
Colorectal cancer is the third most common cancer worldwide, and surgery is the primary treatment. Developing and implementing clinical nursing practice guidelines for preoperative care is essential to enhance patient outcomes. Evidence supports the effectiveness of clinical nursing practice guidelines in Thailand for colorectal surgery, particularly in reducing hospital stays and enhancing quality of life. However, preoperative components such as individualized education, comprehensive nutritional support, and psychological readiness remain insufficiently addressed in existing studies. This study aimed to 1) develop and implement a preoperative clinical nursing practice guideline, 2) evaluate its impact on patients' knowledge, anxiety, behavioral adherence, and satisfaction among both nurses and patients, and 3) assess its feasibility and nurses' and patients' satisfaction. Using Soukup's evidence-based model, the clinical nursing practice guidelines were designed and evaluated through evidence-triggered, evidence-supported, and evidence-observed approaches. The study included 12 nurses and 24 patients with colorectal cancer scheduled for surgery at a university hospital in Bangkok, Thailand. Patients' knowledge and anxiety were measured before and after the initial visit, one week later, and on the day of admission. Behavioral adherence was assessed at one week and admission. The satisfaction of nurses and patients with the guidelines was evaluated. Data were analyzed using descriptive statistics and Friedman and Wilcoxon signed-rank tests. The Preoperative Nursing Practice Guidelines for people with colorectal cancer included four components of recommendations: 1) preadmission information, education, and counseling; 2) preoperative optimization; 3) nutritional assessment; and 4) prehabilitation. The results revealed that patients demonstrated significantly increased knowledge and showed a trend of anxiety reduction, with good behavioral adherence. Both patients and nurses reported high compliance and satisfaction with the guidelines. Nurses can apply these guidelines in practice to care for patients with colorectal cancer. However, further study should include postoperative follow-up of the outcomes with a larger sample size, multicenter studies, and a randomized controlled trial before it can be widely used.